Elimination of trimethoprim from water via anodic oxidation using a platinum anode: Evaluation of process parameters and degradation kinetics - Yalcinyuva, Turker; Erkan, Hanife Sari (TAYLOR & FRANCIS LTD, 2025)
This study evaluates the performance of electrochemical oxidation for the degradation of trimethoprim (TMP) in aqueous solutions using a titanium electrode coated with a platinum (Pt/TiO2) anode and a graphite or TiO2 cathodes, as there has been no study of TMP removal using this electrode pair. The Pt/TiO2 anode and TiO2 cathode showed superior performance and experiments were carried out over a range of applied currents (0.25 to 1.25 A, corresponding to current densities of 4.7 to 23.5 mA/cm2), pH values (3 to 11), oxidation times (0 to 90 min), different electrolyte solutions (NaCl, Na2SO4, NaNO3) and their molarities (0.03, 0.05, 0.07 M), and initial TMP concentrations (5-40 mg/L). Under optimal conditions (pH 6.6, 0.03 M NaCl as supporting electrolyte, 1 A applied current and 90 min reaction time), the TMP degradation efficiencies were 93.23% for 5 mg/L, 96.46% for 10 mg/L, 99.00% for 20 mg/L, 95.64% for 30 mg/L and 94.84% for 40 mg/L. Kinetic analysis indicated a first order reaction model with degradation rate constants of 0.0336 min-1 for 5 mg/L, 0.027 min-1 for 10 mg/L, 0.0439 min-1 for 20 mg/L, 0.0264 min-1 for 30 mg/L and 0.0238 min-1 for 40 mg/L. Mean specific energy consumption (SEC) values were found to be 145.3 +/- 6.6 kWh/m3 for all initial TMP concentrations. SEC values in terms of TMP removed decreased with increasing initial TMP concentrations and varied between 55.9 and 4.2 kWh/mg TMP for initial TMP concentrations between 5 mg/L and 40 mg/L. These results demonstrate that electrochemical oxidation using a Pt/TiO2 anode and TiO2 cathode is a highly effective approach to TMP removal over a range of initial concentrations.
Keywords: Trimethoprim; pharmaceutical; anodic oxidation; platinum anode; degradation kinetics; energy consumption; MUNICIPAL WASTE-WATER; BORON-DOPED DIAMOND; PERSONAL CARE PRODUCTS; ELECTROCHEMICAL OXIDATION; ELECTROCATALYTIC DEGRADATION; ORGANIC POLLUTANTS; ANTIBIOTIC TRIMETHOPRIM; REMOVAL; ELECTRODE; EFFLUENT; Chemistry; Environmental Sciences & Ecology